Evaluation of Parametric Response Mapping to Assess Therapeutic Response to Human Mesenchymal Stem Cells after Experimental Stroke. Issue 8 (August 2017) - He, Rui; Moisan, Anaïck; Detante, Olivier; Rémy, Chantal; Krainik, Alexandre; Barbier, Emmanuel Luc; Lemasson, Benjamin
Stroke is the leading cause of disability in adults. After the very narrow time frame during which treatment by thrombolysis and mechanical thrombectomy is possible, cell therapy has huge potential for enhancing stroke recovery. Accurate analysis of the response to new therapy using imaging biomarkers is needed to assess therapeutic efficacy. The aim of this study was to compare 2 analysis techniques: the parametric response map (PRM), a voxel-based technique, and the standard whole-lesion approach. These 2 analyses were performed on data collected at 4 time points in a transient middle cerebral artery occlusion (MCAo) model, which was treated with human mesenchymal stem cells (hMSCs). The apparent diffusion coefficient (ADC), cerebral blood volume (CBV), and vessel size index (VSI) were mapped using magnetic resonance imaging (MRI). Two groups of rats received an intravenous injection of either 1 mL phosphate-buffered saline (PBS)-glutamine (MCAo-PBS, n = 10) or 3 million hMSCs (MCAo-hMSC, n = 10). One sham group was given PBS-glutamine (sham, n = 12). Each MRI parameter was analyzed by both the PRM and the whole-lesion approach. At day 9, 1 d after grafting, PRM revealed that hMSCs had reduced the fraction of decreased ADC (PRMADC − : MCAo-PBS 6.7% ± 1.7% vs. MCAo-hMSC 3.3% ± 2.4%), abolished the fraction of increased CBV (PRMCBV+ : MCAo-PBS 16.1% ± 3.7% vs. MCAo-hMSC 6.4% ± 2.6%), and delayed the fraction of increased VSI (PRMVSI+ : MCAo-PBS 17.5% ± 6.3% vs. MCAo-hMSC 5.4% ± 2.6%). The whole-lesion approach was, however, insensitive to these early modifications. PRM thus appears to be a promising technique for the detection of early brain changes following treatments such as cell therapy.